2021
DOI: 10.1021/acsabm.1c00982
|View full text |Cite
|
Sign up to set email alerts
|

Smart Metal–Organic Frameworks for Biotechnological Applications: A Mini-Review

Abstract: In this pandemic situation it is evident that viruses and bacteria, more specifically, multiple drug resistant (MDR) bacteria, endanger human civilization severely. It is high time to design smart weapons to combat these pathogens for the prevention and cure of allied ailments. Metal–organic frameworks (MOFs) are porous materials designed from metal ions or inorganic clusters and multidentate organic ligands. Due to some unique features like high porosity, tunable pore shape and size, numerous possible metal-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 129 publications
(149 reference statements)
0
10
0
Order By: Relevance
“…In this case, the usage of adsorbents is one of the potential options for resolving this problem. , Nanoporous biomaterials, including MOFs or porous coordination polymers (PCPs), have a considerable performance in this field . The structure of MOFs is a link of metal ions and organic linkers by coordination bonds, which could construct a high surface area and a wide range of different pore sizes in various structures. Elasticity, three-dimensional structure, a large surface area, pore size, and surface polarity variability are the characteristics that are strongly associated with the best choice of organic ligand/metal ion combinations. The main reason that MOFs have attracted attention is doubtlessly the various applications of this material in different fields of study, including gas storage and separation, surface adsorption, ion exchange, sensors, drug delivery, catalysis, optical and magnetic material, and chromatography. Among MOF materials, IRMOF-1 is the most studied because of its great capacity for organic material adsorption as a metal–organic framework. Furthermore, it is famous for its excellent strength, fluidity properties, extreme porosity and well-ordered construction, great thermal stability, and flexibility in chemical functional groups. , These characteristics stem from the construction of IRMOF-1, which includes a large and inflexible secondary building unit, as well as benzene links, and results in exceptionally high porosity and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the usage of adsorbents is one of the potential options for resolving this problem. , Nanoporous biomaterials, including MOFs or porous coordination polymers (PCPs), have a considerable performance in this field . The structure of MOFs is a link of metal ions and organic linkers by coordination bonds, which could construct a high surface area and a wide range of different pore sizes in various structures. Elasticity, three-dimensional structure, a large surface area, pore size, and surface polarity variability are the characteristics that are strongly associated with the best choice of organic ligand/metal ion combinations. The main reason that MOFs have attracted attention is doubtlessly the various applications of this material in different fields of study, including gas storage and separation, surface adsorption, ion exchange, sensors, drug delivery, catalysis, optical and magnetic material, and chromatography. Among MOF materials, IRMOF-1 is the most studied because of its great capacity for organic material adsorption as a metal–organic framework. Furthermore, it is famous for its excellent strength, fluidity properties, extreme porosity and well-ordered construction, great thermal stability, and flexibility in chemical functional groups. , These characteristics stem from the construction of IRMOF-1, which includes a large and inflexible secondary building unit, as well as benzene links, and results in exceptionally high porosity and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…[18] MOFs are a new type of material with a porous and tunable structure. [19] In recent years, they have been widely used to catalyze the cracking of water, [20,21] reduction of carbon dioxide, [22] and also been used as carriers for drugs. [23] Researchers found that the Fenton reaction catalyzed by Fe 2+ has a high pH dependence and it exerts excellent effects under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The development of organic ligands having a higher structural complexity is one of the main directions in order to prepare MOFs showing advanced functionalities [31][32][33][34]. Thus, the incorporation of stimuli-responsive scaffolds inside a MOF matrix turned out to be an ideal strategy within reticular chemistry [35][36][37][38], allowing to prepare smart materials [39,40]. The application of an external stimulus induces changes in the organic ligands, leading to modifications of certain properties of the metal-organic material, such as porosity [41,42].…”
Section: Introductionmentioning
confidence: 99%